Childhood rectal carcinoma (Bangladesh Medical Journal Khulna, 2012)
Carcinoma of rectum in an 11 years old male child is presented with a history of bleeding per rectum, constipation and lower abdominal pain. Colorectal carcinoma in childhood is rare and the reported incidence is about 1.3 per million lives. Its clinical, pathologic and histological characteristics are different from those of adults. The prognosis is poorer in children, the reason for which it is explained with a brief discussion. DOI: http://dx.doi.org/10.3329/bmjk.v43i1-2.13020 Bang Med J (Khulna) 2010; 43: 24-25